Perlindungan Sengketa Konsumen Menurut Undang-Undang Nomor 8 Tahun 1999 - Miasiratni Miasiratni (Universitas Sumatera Barat, 2024)
Legal certainty to provide protection to consumers in the form of protection of consumer rights, which is strengthened through special legislation, namely the Consumer Protection Law, gives hope that business actors will not act arbitrarily which always harms consumer rights. Law no. 8 of 1999 concerning Consumer Protection regulates consumer protection. Based on Article 1 point 1, it is stated that consumer protection is all efforts to ensure legal certainty to provide protection to consumers. The Consumer Dispute Protection Agency is tasked with resolving consumer disputes both through litigation and non-litigation. This method uses a normative juridical method, namely by providing a clear, systematic picture of various matters relating to the duties of the Consumer Dispute Resolution Agency according to Law No. 8 of 1999 concerning consumer protection. The results of this research show that the Consumer Dispute Resolution Agency (BPSK) according to Law NO 8 of 1999 is the body tasked with handling and resolving disputes between business actors and consumers. Consumer dispute resolution body (BPSK) is a special institution formed by the government in level II regions to resolve consumer disputes outside of court.